Ambient temperature structures the gut microbiota of zebrafish to impact the response to radioactive pollution. (15th January 2022) - Wang, Bin; Zhang, Shu-qin; Dong, Jia-li; Li, Yuan; Jin, Yu-xiao; Xiao, Hui-wen; Wang, Hai-chao; Fan, Sai-jun; Cui, Ming
Abstract: Potential nuclear accidents propel serious environmental pollution, and the resultant radionuclide release devastates severely the environment severely and threatens aquatic organism survival. Likewise, ongoing climate change coupled with the gradual increase in global surface temperatures can also adversely impact the aquatic ecosystems. In the present study, we preconditioned zebrafish ( Danio rerio ) at three different temperatures (18 °C, 26 °C and 34 °C) to investigate the effects of a temperature profile on their radiosensitivity (exposure to 20 Gy of gamma rays) to identify the potential biochemical mechanism responsible for influencing radiosensitivity. We found that preconditioning of zebrafish at different temperatures moulded specific gut microbiota configurations and impacted hepatic glycometabolism and sensitivity to subsequent radiation. Following antibiotic treatment to reduce gut bacteria, these observed differences in the expression of hepatic glycometabolism-related genes and radiation-induced intestinal toxicity were minimal, supporting the hypothesis that the gut bacteria reshaped by different ambient temperatures might be the key modulators of hepatic functions and radiosensitivity in zebrafish. Together, our findings provide novel insights into the connection of radiation injuries with temperature alterations in fish, and suggest that maintaining the stability of gram-positive bacteria may be efficacious to protect aquatic organisms against short or long-term radioactive contamination in the context of global climate change. Graphical abstract: Image 1 Highlights: Thermal preconditionings alter the gut bacterial configurations of zebrafish. Thermal preconditionings affect the response of zebrafish to radiation exposure. High temperature enriches gut microbiota with greater glycometabolism in zebrafish. Gut microbiota governs the hepatic glycometabolism and radiosensitivity of zebrafish. Gut gram-positive bacteria promote the radioprotection of low-temperature preconditioning. Abstract : Our study found alterations in the radiosensitivity of zebrafish exposed to gamma rays induced by temperature preconditioning depended partly on gut bacteria, with gram-positive bacteria playing a vital role.